INTEGRATING CHATBOTS IN CREATIVE DESIGN LEARNING - Bareja, Lakshay; Subhashini R; Saroha, Sangeet; Rani, Sudha; Joshi, Chaitanya; Arora, Sonia; Sule, Bipin (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The introduction of chatbot technologies in the creative design learning setting is transforming the way students formulate, test and develop artistic ideas. The more conversational AI agents develop, the more they become interactive collaborative creators that are able to offer real-time feedback, create alternative design paths, and improve reflective thinking. This paper focuses on the educational utility of chat bots in stimulating creativity, exploration in design, and problem solving in educational and job training settings. The analysis of the multimodal interaction patterns, adaptive guidance mechanisms, and personalized scaffolding also helps the research to clarify the role of chatbots in enhancing the learning experience in a traditional studio setting. The results reveal that chatbot facilitated workflows are highly effective in enhancing the ideation fluency, visual reasoning, and speed of iteration among learners, and decrease the cognitive load when performing complicated design tasks. In addition, chatbots promote more learner agency by allowing learners to have unlimited access to feedback, sources, and context-based design recommendations. The dilemmas of excessive reliance on computerized feedback, possible bias in the results of artificial intelligence, and the necessity to have open-evaluation standards are also addressed. The suggested framework supports the idea of including chatbots as a learning partners and not as didactic substitutes, and a balanced human-AI co-creation model. On the whole, the study is an addition to the developing field of literature on intelligent creative pedagogy and proves that chatbots have a significant potential to improve engagement, experimentation, and learning outcomes in creative design education.